Experimental study of machinability of GFRP composites by end milling - Azwan Iskandar, Azmi; Lin, Richard J.T.; Bhattacharyya, Debes (Taylor and Francis Group, LLC., 2012)
Link to publisher's homepage at http://www.tandfonline.com/